The art of horror movies : an illustrated history - Jones, Stephen, 1953-; Landis, John, 1950- (Milwaukee, WI : Applause Theatre & Cinema Books, an imprint of Hal Leonard LLC, 2017)
This magnificent companion to The Art of Horror , from the same creative team behind that award-winning illustrated volume, looks at the entire history of the horror film, from the silent era right up to the latest releases and trends. Through a series of informative chapters and fascinating sidebars chronologically charting the evolution of horror movies for more than a century, profusely illustrated throughout with over 600 rare and unique images including posters, lobby cards, advertising, promotional items, tie-in books and magazines, and original artwork inspired by classic movies, this handsomely designed hardcover traces the development of the horror film from its inception, and celebrates the actors, filmmakers, and artists who were responsible for scaring the pants off successive generations of moviegoers! Edited by multiple award-winning writer and editor Stephen Jones, and boasting a foreword by director and screenwriter John Landis ( An American Werewolf in London ), this volume brings together fascinating and incisive commentary from some of the genre's most highly respected experts. With eye-popping images from all over the world, The Art of Horror Movies is the definitive guide for anyone who loves horror films and movie fans of all ages
Foreword: The Iconography f Horror / By John Landis -- Introduction: Painting with Light and Shadows / By Stephen Jones -- The Sinister Silents. Silent Screams and German Expressionism / By Sir Christopher Frayling -- The Thrilling Thirties. The Kings of Horror and Universial Studios / By Tom Weaver -- The Frightening Forties. Noir Nightmares and Poverty-Row Horros / By Barry Forshaw -- The Fearsome Fifties. Atomic Aliens and Technicolor Terrors / By David J. Schow -- The Stylish Sixties. AIP, Hammer, Amicus, and Tigon / By Kim Newman -- The Satanic Seventies. Vivacious Vampire and Demonic Damsels / By Jonathan Rigby -- The Evil Eighties. Freddy. Michael, Jason and Friends / By Lisa Morton -- The Nasty Nineties. Remakes, Re-imaginings, and Retribution / By Anne Billson -- The 2000s Maniacs. Hand-Held Horrors and Foreign Frights / By Ramsey Campbell
Includes index
Keywords: Horror films -- History and criticism; Art in motion pictures